The Trivalent Copper Complex of a Conjugated Bis-dithiocarbazate Schiff Base: Stabilization of Cu in Three Different Oxidation States - Akbar Ali, Mohammad; Bernhardt, Paul V; Brax, Mathilde A. H; England, Jason; Farlow, Anthony J; Hanson, Graeme R; Yeng, Lee Len; Mirza, Aminul Huq; Wieghardt, Karl (Inorganic chemistry, 2013)
The new tribasic N2S2 ligand H3ttfasbz has been synthesized by condensation of 4-thenoyl 2,2,2-trifluoroacetone and S-benzyl dithiocarbazate. On complexation with copper(II) acetate, spontaneous oxidation to the CuIII oxidation state is observed, and the complex [Cu(ttfasbz)] has been isolated and characterized structurally. Reduction to the EPR active CuII analogue has been achieved chemically and also electrochemically, and in both cases, the process is totally reversible. The CuIII/II redox potential of the complex is remarkably low and similar to that of the ferrocenium/ferrocene couple. Further reduction to the formally monovalent (d 10) dianion [CuI(ttfasbz)]2– may be achieved electrochemically. Computational chemistry demonstrates that the three redox states [Cu(ttfasbz)], [Cu(ttfasbz)]−, and [Cu(ttfasbz)]2– are truly CuIII, CuII, and CuI complexes, respectively, and the potentially noninnocent ligand does not undergo any redox reactions.